2018
DOI: 10.3324/haematol.2017.181024
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling reveals a close relationship between follicular lymphoma grade 3A and 3B, but distinct profiles of follicular lymphoma grade 1 and 2

Abstract: A linear progression model of follicular lymphomas (FL) FL1, FL2 and FL3A has been favored, since FL3A often co-exist with an FL1/2 component. FL3B, in contrast, is thought to be more closely related to diffuse large B-cell lymphoma (DLBCL), and both are often simultaneously present in one tumor (DLBCL/FL3B). To obtain more detailed insights into follicular lymphoma progression, a comprehensive analysis of a well-defined set of FL1/2 (n=22), FL3A (n=16), FL3B (n=6), DLBCL/FL3B (n=9), and germinal center B-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 27 publications
4
31
0
Order By: Relevance
“…6,9,20 Furthermore, a previous study noted that FL 3B differed from FL 1-3A with distinct cytogenetic and immunohistochemical features, 21 while further study suggested that FL 3B harboured similar gene expression profiles as FL 3A. 3 Despite these promising results, the prognostic value of grades is controversial and whether FL 3A is more closely associated with 3B remains to be elucidated.…”
Section: Ki-67 Correlation With Outcome and Gradesmentioning
confidence: 99%
See 2 more Smart Citations
“…6,9,20 Furthermore, a previous study noted that FL 3B differed from FL 1-3A with distinct cytogenetic and immunohistochemical features, 21 while further study suggested that FL 3B harboured similar gene expression profiles as FL 3A. 3 Despite these promising results, the prognostic value of grades is controversial and whether FL 3A is more closely associated with 3B remains to be elucidated.…”
Section: Ki-67 Correlation With Outcome and Gradesmentioning
confidence: 99%
“…2 In contrast, gene expression profiles showed that FL 3A closely resembled FL 3B rather than FL 1-2. 3 A much-debated question is the prognostic value of histological grading in FL. Some studies have revealed that higher grades correlated with inferior outcomes, 4,5 whereas other studies suggested that histological grade did not predict the outcome of FL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous transcriptomic study observed a relatively homogeneous gene expression profiling in the different histological grades of FL, but also identified differences between FL1‐3A and FL3B (Piccaluga et al , ). Although some differences in coding gene expression profiles have also been described between FL1‐2 and FL3A, these FL subtypes are also closely related, as also shown at the genetic and immunohistochemical level (Horn et al , ). Non‐coding RNA expression profiling studies in FL have basically analysed expression and sequence alterations of microRNAs (Musilova & Mraz, ; Hezaveh et al , ).…”
mentioning
confidence: 91%
“…Gene expression profiling has also revealed significantly different expression signatures between low-grade (I and II) and high-grade (IIIA and IIIB) FL suggesting that grade I-II and grade III FL may represent different biological entities. [ 35 ].…”
Section: Discussionmentioning
confidence: 99%